Viabilidade técnico-econômica da turbina eólica offshore - Oliveira, Thamires de Almeida (2019)
This work develops a techno-economic analysis of a fixed bottom offshore wind turbine in the Southeast and Northeast regions of Brazilian. Initially, the environmental data of the selected locations such as wind and wave regimes and sea depth are obtained using global models. Subsequently, this data is used through the FAST software to analyze the hydrodynamic and structural behavior of the wind turbine. Afterward, economic analyses are performed to calculate the costs of the turbine, foundation, electrical infrastructure, and operation and maintenance during the wind turbine’s lyfecycle, which is assumed to be twenty years. The dissertation finally compares the energy production costs in Brazil concerning other countries that already have this type of energy to evaluate the price competitiveness.